SARS-CoV-2 and the Host Cell: A Tale of Interactions - Pizzato, Massimo; Baraldi, Chiara; Boscato Sopetto, Giulia; Finozzi, Davide; Gentile, Carmelo; Gentile, Michele Domenico; Marconi, Roberta; Paladino, Dalila; Raoss, Alberto; Riedmiller, Ilary; Ur Rehman, Hamza; Santini, Annalisa; et al. (Frontiers in Virology, 2022)
The ability of a virus to spread between individuals, its replication capacity and the clinical course of the infection are macroscopic consequences of a multifaceted molecular interaction of viral components with the host cell. The heavy impact of COVID-19 on the world population, economics and sanitary systems calls for therapeutic and prophylactic solutions that require a deep characterization of the interactions occurring between virus and host cells. Unveiling how SARS-CoV-2 engages with host factors throughout its life cycle is therefore fundamental to understand the pathogenic mechanisms underlying the viral infection and to design antiviral therapies and prophylactic strategies. Two years into the SARS-CoV-2 pandemic, this review provides an overview of the interplay between SARS-CoV-2 and the host cell, with focus on the machinery and compartments pivotal for virus replication and the antiviral cellular response. Starting with the interaction with the cell surface, following the virus replicative cycle through the characterization of the entry pathways, the survival and replication in the cytoplasm, to the mechanisms of egress from the infected cell, this review unravels the complex network of interactions between SARS-CoV-2 and the host cell, highlighting the knowledge that has the potential to set the basis for the development of innovative antiviral strategies.